Structurally Constrained MUC1‐Tn Mimetic Antigen as Template for Molecularly Imprinted Polymers (MIPs): A Promising Tool for Cancer Diagnostics. Issue 9 (3rd May 2022) - Palladino, Pasquale; Papi, Francesco; Minunni, Maria; Nativi, Cristina; Scarano, Simona
Abstract: Abnormal glycoconjugates have distinctly been recognized as potential biomarkers for cancer diagnosis. A great deal of attention has been focused on Tn antigen, an oversimplified mucin‐1 O ‐glycan, over‐expressed in different cancers. Herein, we investigate the possibility to replace the use of anti‐Tn monoclonal antibodies with an innovative class of catecholamine‐based Molecularly Imprinted Polymers (MIPs), emerging in recent years as promising tools for bioanalytical applications. MIPs are synthetic receptors characterized by high sensitivity and specificity towards the imprinted target. Here, original polynorepinephrine‐based MIPs coupled to Surface Plasmon Resonance biosensing for Tn antigen recognition are reported. We have verified the imprinting and binding capacity of these MIPs towards very small antigenic entities, represented by the natural Tn antigen and the TnThr mimetic 1 (conjugated to BSA or linked to a MUC1 hexapeptide analogue), and compared the biosensor performances with an anti‐Tn monoclonal antibody. The results clearly display the effectiveness of the pursued imprinting strategies. Abstract : A structurally constrained α‐Tn antigen mimetic 1, as monomer or linked to a MUC1 hexapeptide, has been selected as template to imprint polynorepinephrine (PNE). The imprinting and binding capacity of the PNE‐MIPs so obtained have been screened towards very small antigenic entities, like the natural Tn antigen and the TnThr mimetic 1, or towards 1 MUC1 hexapeptide analogues.